Television Programmes in the Acquisition of English Pronunciation - Zdena Kralova; Rastislav Metruk (Communications - Scientific letters of the University of Zilina, 2010)
The study analyzes the influence of watching authentic TV programmes in English on the non-native speakers’ level of English pronunciation. We tried to detect the correlation between frequency of watching TV programmes and perceptual analysis of English pronunciation of our respondents which was done by native speakers.